2018
DOI: 10.1186/s13195-018-0394-7
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease master regulators analysis: search for potential molecular targets and drug repositioning candidates

Abstract: BackgroundAlzheimer’s disease (AD) is a multifactorial and complex neuropathology that involves impairment of many intricate molecular mechanisms. Despite recent advances, AD pathophysiological characterization remains incomplete, which hampers the development of effective treatments. In fact, currently, there are no effective pharmacological treatments for AD. Integrative strategies such as transcription regulatory network and master regulator analyses exemplify promising new approaches to study complex disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 90 publications
1
46
0
1
Order By: Relevance
“…Nuclear receptor subfamily 4 group A member 3 has been involved in Lewy body disease and multiple system atrophy [86]. TSC22D1 is a pro-apoptotic tumor suppressor transcription factor induced by transforming growth factor β (TGFβ), that was found as putatively involved in AD pathophysiology in an unbiased network analysis of transcription factors and their targets [87] and was also present in our acute injury-DOWN signature. The presence of App (encoding the amyloid β precursor protein or AβPP) in the neurodegeneration-UP signature is intriguing and cannot just be explained by a leakage of the APP transgene expression to astrocytes in AβPP-overexpressing AD mouse models [88], because it was also notably upregulated in other mouse models such as SOD1-G93A ALS mice.…”
Section: Discussionmentioning
confidence: 97%
“…Nuclear receptor subfamily 4 group A member 3 has been involved in Lewy body disease and multiple system atrophy [86]. TSC22D1 is a pro-apoptotic tumor suppressor transcription factor induced by transforming growth factor β (TGFβ), that was found as putatively involved in AD pathophysiology in an unbiased network analysis of transcription factors and their targets [87] and was also present in our acute injury-DOWN signature. The presence of App (encoding the amyloid β precursor protein or AβPP) in the neurodegeneration-UP signature is intriguing and cannot just be explained by a leakage of the APP transgene expression to astrocytes in AβPP-overexpressing AD mouse models [88], because it was also notably upregulated in other mouse models such as SOD1-G93A ALS mice.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have indicated that the p38 MAPK/ATF-2 signaling pathway induces COX-2-derived PGE2 production during inflammatory responses in brain injury and in inflammatory diseases [ 41 ]. Accordingly, ATF-2 may potentially function as a critical molecular target for drug therapies in neurodegenerative diseases [ 42 ]. Taken together, our data demonstrate that a Ca 2+ -dependent βCaMΚΙΙ response appears to provide a bridge between stress exposure and neuroinflammatory activation.…”
Section: Discussionmentioning
confidence: 99%
“…The ELMER analysis exploits the interplay between DNA methylation and transcription factor binding at distal regulatory sites to identify potential master regulator transcription factors that may help explain how microdeletion has such widespread functional consequences. Therefore, identifying master regulator transcription factors provides insight into complex biological outcomes through the regulation of multiple genes, and these transcription factors could serve as targets for the development of novel therapeutic approaches [ 38 ]. Through ELMER analysis, we identified BCL11A as a potential upstream master regulator transcription factor.…”
Section: Discussionmentioning
confidence: 99%